Jean Bernier Gallery 1977-1998. - Bernier, Jean; Colombo, Paolo; Eliades, Marina; Janus, Elizabeth; Petsopoulos, Stavros; Sarris, Kyrillos; Zacharopoulos, Denys; Jean Bernier - Marina Eliades Gallery, Athene (Athens : Agra Publications - Stavros Petsopoulos, 1998)
Abramovic, Marina ; Akrithakis, Alexis ; Andre, Carl ; Anselmo, Giovanni ; Antonakos, Stephen ; Baikas, Nicos ; Barth, Jack ; Beecroft, Vanessa ; Bochner, Mel ; Boltanski, Christian ; Buthe, Michael ; Calzolari, Pierpaolo ; Caniaris, Vlassis ; Casebere, James ; Charlton, Alan ; Christodoulou, Eleni ; Colombo, Paolo ; Dibbets, Jan ; Ernst, Max ; Riverhead (New York) ; Floeter, Kent ; Frère, Michel ; Fujita, Kenji ; Genzken, Isa ; Gilbert & George ; Gober, Robert ; Gursky, Andreas ; Hagenberg, Helfried ; Heard, Andrew ; Hunt, Bryan ; Judd, Donald ; Jung, Klaus ; Iglesias, Cristina ; Kapsalis, Michael ; Kavallieratos, Takis & Stella ; Klingelhöller, Harald ; Kounellis, Jannis ; Laib, Wolfgang ; Lappas, George ; Levav, Ruven ; Leroy, Eugène ; Long, Richard ; Mangold, Robert ; Marden, Brice ; Mattiacci, Eliseo ; Merz, Mario ; Merz, Marisa ; Muñoz, Juan ; Nauman, Bruce ; Oursler, Tony ; Paolini, Giulio ; Poitevin, Eric ; Quinn, Marc ; Richter, Gerhard ; Rückriem, Ulrich ; Samaras, Lucas ; Schütte, Thomas ; Serra, Richard ; Silverman, Martin ; Simiriotis, Yannis ; Simoni, Mariella ; Stadtbäumer, Pia ; Stamos, Theodoros ; Taylor, Marcus ; Tirelli, Marco ; Tsekouras, Vassiliki ; Tsiaras, Philip ; Turrell, James ; van Elk, Ger ; Vermeiren, Didier ; Webb, Boyd ; Weiner, Lawrence ; West, Franz ; Williams, Sue ; Wood, William ; Wool, Christopher ; Xenos, Jorgos ; Chen Zhen ; Zogolopoulos, George ; Zorio, Gilberto
biografie
Engels
boek